Modeling of Adhesively Bonded Joints - da Silva, Lucas F. M. (Springer Berlin Heidelberg : Imprint: Springer, 2008)
A lot of recent developments have been made about adhesively bonded joints modeling using various methods of analysis. The increasing application of adhesives in industry is partly due to the increased sophistication and reliability of adhesive joints modeling. The book proposed intends to provide the designer with the most advanced stress analyses techniques in adhesive joints to reinforce the use of this promising bonding technique.